2020
DOI: 10.1136/bmjresp-2020-000595
|View full text |Cite|
|
Sign up to set email alerts
|

Exploratory cost-effectiveness model of electromagnetic navigation bronchoscopy (ENB) compared with CT-guided biopsy (TTNA) for diagnosis of malignant indeterminate peripheral pulmonary nodules

Abstract: IntroductionLung cancer is accountable for 35 000 deaths annually, and prognosis is improved when the cancer is diagnosed early. CT-guided biopsy (transthoracic needle aspiration, TTNA) and electromagnetic navigation bronchoscopy (ENB) can be used to investigate indeterminate pulmonary nodules if the patient is unfit for surgery. However, there is a paucity of clinical and health economic evidence that directly compares ENB with TTNA in this population group. This cost-effectiveness study aimed to explore pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…As has been mentioned in reviews (12), a combination of factors is essential for bronchoscopic diagnosis of pulmonary nodules: (I) selecting the correct airway to reach the target (navigation), (II) approaching the target as close as possible (peripheral access), (III) confirming the location of the target before sampling (confirmation), and (IV) sampling the same place as confirmed prior (realtime feedback). As a navigational modality, robust evidence on ENB has accumulated regarding its safety (15,24), diagnostic performance (15,19), and cost-effectiveness (28).…”
Section: Resultsmentioning
confidence: 99%
“…As has been mentioned in reviews (12), a combination of factors is essential for bronchoscopic diagnosis of pulmonary nodules: (I) selecting the correct airway to reach the target (navigation), (II) approaching the target as close as possible (peripheral access), (III) confirming the location of the target before sampling (confirmation), and (IV) sampling the same place as confirmed prior (realtime feedback). As a navigational modality, robust evidence on ENB has accumulated regarding its safety (15,24), diagnostic performance (15,19), and cost-effectiveness (28).…”
Section: Resultsmentioning
confidence: 99%
“…Our decision analytical model shows that CBCT-NB can be a cost-effective diagnostic modality in the workup of intermediate risk PNs both when directly compared with CT-guided transthoracic biopsy, and when compared with direct treatment (without pathology proven malignancy) in TTNB ineligible patients. A cost-effectiveness study on electromagnetic navigation bronchoscopy (EMN) by Rickets et al 26 showed that EMN was expected to be cost-effective if EMN could obtain the same diagnostic accuracy as TTNB. Our study confirms these findings.…”
Section: Discussionmentioning
confidence: 99%
“…In case of no malignancy at baseline, health utilities of a Dutch healthy 65 years old were used 18. Utility loss due to TTNB or CBCT-NB were based on complications and associated utility loss 26. Following VATS or SABR, an initial utility loss representing the direct impact of treatment was followed by a yearly less pronounced utility loss reflecting long-term consequences 27 28.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth mentioning that a cohort study revealed that ENB is more cost-effective when the likelihood of an accurate diagnosis is equal to that of TTNA. This can happen in certain subgroups in whom TTNA is unlikely to achieve an accurate diagnosis, or is performed by experienced operators to reach a high accuracy with ENB [85].…”
Section: Lungcare Navigation Systemmentioning
confidence: 99%